Pengaruh Kelicahan Kaki terhadap Ketepatan Pukulan Forehand Drive pada Olahraga Tenis Meja - Kurniadi, Agus; Istiyono; Jems; Vadel (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2025)
This study aims to determine the effect of foot agility on the accuracy of the forehand drive in table tennis athletes. The research employed a quantitative approach with a correlational design. The sample consisted of 30 Physical Education students from Universitas Muhammadiyah Sorong. The instruments used were the Illinois Agility Test and a forehand drive accuracy test. Data were analyzed using the Pearson Product Moment correlation. The results showed a significant effect of foot agility on forehand drive accuracy (r = 0.61; p < 0.05). These findings indicate that students with better foot agility are able to position their bodies more optimally before striking the ball. Additionally, effective foot coordination enhances reaction time to incoming balls. Overall, footwork performance contributes strongly to the stability and accuracy of the forehand drive